The Concept of TPACK through Exchange Orientation Program in Boosting Madrasa Student Achievements - Hidayat, Wildan Nur; Kusminin, Kusminin; Taufik, Taufik; Nurjali, Nurjali; Mun'amah, Anatun Nisa (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This qualitative study investigates the application of the Technological Pedagogical and Content Knowledge (TPACK) framework through an Exchange Orientation program designed to enhance student achievement in madrasahs. The research employs in-depth interviews and focus group discussions with educators participating in the program to gather insights into their experiences and perceptions regarding the integration of technology in teaching practices. The findings reveal that the Exchange Orientation program fosters collaborative learning among teachers, enabling them to share effective strategies for incorporating technology into their pedagogy and content delivery. Participants reported increased confidence in using technological tools, which subsequently led to more engaging and interactive learning experiences for students. The study highlights the critical role of professional development initiatives that utilize the TPACK framework in transforming teaching methodologies and improving student learning outcomes in madrasahs.